A Study on corruption and entrepreneurship - KIM, Oksana (KDI School, 2015)
Corruption is one of the important factors affecting country’s economic growth and development. Mostly people tend to perceive corruption negatively as it is believed that corruption is detrimental for economic growth and development of the country as it discourages investments and deteriorates people’s values and beliefs. This study investigates whether corruption should be perceived as negative phenomenon, or there are favorable sides of corruption that can positively contribute to country’s development, particularly in developing countries. Given study uses 3 models linear regression OLS, fixed panel model and random panel model with two continuous variables from 2004 to 2009 to test if there is any positive correlation between level of corruption and entrepreneurial activities in the country, utilizing CPI index, GEM and WBGES data. The analysis of WBGES data revealed, in support of previous studies, that corruption negatively affects entrepreneurship, nevertheless, the correlation was weak. On the other hand, there was an evidence that corruption has positive correlation with entrepreneurship according to GEM dataset and country specific data analysis which doubts unflinching idea of negative sides of corruption.
Thesis(Master) --KDI School:Master of Development Policy,2015